Mindful eating is associated with a healthier plant-based diet in the NutriNet-Santé study - Pauline Paolassini-Guesnier; Marion Van Beekum; Emmanuelle Kesse-Guyot; Julia Baudry; Rebecca Shankland; Angélique Rodhain; Alice Bellicha; Christophe Leys; Serge Hercberg; Mathilde Touvier; Benjamin Allès; Sandrine Péneau (Scientific Reports)
Abstract Scientific evidence suggests that mindful eating (ME) may be effective for promoting healthy plant-based diets. However, data are scarce. This cross-sectional study investigated the association between ME and plant-based diets. In 2023, 13,768 participants from the NutriNet-Santé cohort completed the Mind-Eat Scale, at least three 24-hour dietary records, and a food choices questionnaire. The contribution of plant-based foods was evaluated using the Plant-based Diet Index (PDI), the healthy PDI (hPDI), and the unhealthy PDI (uPDI). Multivariable linear and logistic regressions were performed to analyze the association between ME, the PDI, hPDI, and uPDI scores, the proportions of meat, fish, and dairy products in the diet, and diet groups, adjusting for socio-demographic and lifestyle factors. ME was positively associated with PDI (β = 1.19; 95%CI: 0.98, 1.41) and hPDI (1.00; 0.76, 1.24), and negatively with uPDI (-0.48; -0.70, -0.27), meat (-0.63; -0.76, -0.50), and dairy (-0.86; -1.14, -0.58) consumption. Individuals with higher ME levels were more likely to be lower meat eaters (OR = 1.13; 95%CI: 1.04, 1.23), pesco-vegetarians (1.56; 1.33, 1.83), vegetarians (2.19; 1.57, 3.05), or vegans (1.35; 1.24, 1.48). Participants with higher ME levels were more likely to follow healthy plant-based diets, suggesting ME could help to promote a reduction in animal product consumption. Longitudinal studies are needed to continue exploring this relationship. Clinical Trial Registry: The NutriNet-Santé study was conducted in accordance with the Declaration of Helsinki, and all procedures were approved by the Institutional Review Board of the French Institute for Health and Medical Research (IRB Inserm n◦ 0000388FWA00005831) and the Commission Nationale de l’Informatique et des Libertés (CNIL n◦ 908450 and n◦ 909216). Electronic informed consent was obtained from all participants. Written informed consent by electronic means for adults, and for legal representant for children < 18 years old. The study was registered at clinicaltrials.gov as #NCT03335644 ( https://clinicaltrials.gov/study/NCT03335644?locStr=Bobigny,%20France&country=France&state=%C3%8Ele-de-France&city=Bobigny&term=Cohort%20Study&rank=6 ).